Freshwater molluscs from the Late Neogene Siwalik Group, Surai Khola, western Nepal (Journal of Nepal Geological Society, 1998)
The fossil freshwater molluscs collected from the Siwalik (Churia) Group, along the Surai Khola section, western Nepal, are systematically studied. The molluscan fauna is represented by gastropods belonging to family Viviparidae, Ampullariidae , Bithyniidae, Thiaridae, and bivalves belonging to family Unionidae, Corbiculidae and Pisidiidae. Four new species Angulyagra shiddarthai, Brotia dobataensis, Paludomus suraiensis and Parreysia chureii are described in this paper.